2004
DOI: 10.1517/14656566.5.9.1979
|View full text |Cite
|
Sign up to set email alerts
|

A review of olopatadine for the treatment of ocular allergy

Abstract: Ocular allergy affects > 20% of the general population and many therapeutic preparations are available to individuals experiencing the most common forms--seasonal and perennial allergic conjunctivitis. 0.1% Olopatadine topical ophthalmic solution is currently approved for the treatment of allergic signs and symptoms in patients > or = 3 years of age. Olopatadine is available in Europe as Opatanol) and in > 30 other countries as Patanol. It inhibits mast cell degranulation and antagonises histamine receptors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…Steroids can be highly effective, but there are risks of glaucoma, superinfection with viruses and bacteria due to local immunosuppression, delayed wound healing, and cataract induction warrant cautious use of topical steroids [17][18][19][20][21][22][23][24]. Therefore, non-steroidal medications are desirable for the treatment of VKC as alternative, but new topical agents with dual antiallergic activity (mast cell stabilizers and antihistamine) may also be used for long-term treatment of allergic inflammation to alleviate signs and symptoms of the disease [21,25,26]. A recent study has reported that topical interferon alpha 2b treatment seems to offer a safe and effective alternative for the treatment of refractory vernal keratoconjunctivitis for a brief period [27].…”
Section: Discussionmentioning
confidence: 99%
“…Steroids can be highly effective, but there are risks of glaucoma, superinfection with viruses and bacteria due to local immunosuppression, delayed wound healing, and cataract induction warrant cautious use of topical steroids [17][18][19][20][21][22][23][24]. Therefore, non-steroidal medications are desirable for the treatment of VKC as alternative, but new topical agents with dual antiallergic activity (mast cell stabilizers and antihistamine) may also be used for long-term treatment of allergic inflammation to alleviate signs and symptoms of the disease [21,25,26]. A recent study has reported that topical interferon alpha 2b treatment seems to offer a safe and effective alternative for the treatment of refractory vernal keratoconjunctivitis for a brief period [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ketotifen, which is well tolerated at lower doses, has nonspecific cytotoxic effects on the histamine release by mast cells at higher doses [15]. In contrast, olopatadine has a demonstrable effect on nasal allergy symptoms addressing the ocular pathology but is under study for the management of eyelid swelling due to allergy [3]. The benefit in trying products of different classes and/or their combination to control ocular allergy is evident since multiple cascades are involved in eliciting allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic conjunctivitis is one of the most common ocular allergic diseases and is known to affect more than 20% of the population [1,2,3]. Recently, due to changes in living environment and other reasons, the number of patients with allergic diseases, including pollinosis, is showing an upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new anti-allergic compounds have been demonstrated to possess both activities and even more. Olopatadine, for example, is a histamine H 1 -receptor antagonist and its ability to stabilize mast cells has been demonstrated both in vitro and in vivo [4]. Moreover, it reduces histamine-induced production of IL-6 and IL-8 by conjunctival epithelial cells and inhibits conjunctival mast cell upregulation of ICAM-1 driven by anti-IgE on conjunctival epithelial cells in vitro [24].…”
Section: Discussionmentioning
confidence: 99%